2019
DOI: 10.3390/jcm8101519
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Inflammasome Activation in Dilated Cardiomyopathy

Abstract: Background: The clinical outcome of patients affected by dilated cardiomyopathy (DCM) is heterogeneous, since its pathophysiology is only partially understood. Interleukin 1β levels could predict the mortality and necessity of cardiac transplantation of DCM patients. Objective: To investigate mechanisms triggering sterile inflammation in dilated cardiomyopathy (DCM). Methods: Hearts explanted from 62 DCM patients were compared with 30 controls, employing immunohistochemistry, cellular and molecular biology, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
(72 reference statements)
1
40
0
Order By: Relevance
“…A line crossing the centre of nuclei was drawn and the length of the segment crossing the opposite intercalated discs was then measured, in analogy to what has been described in Vliegen et al, 14 and published by us recently. 15 Vascular density was assessed by counting capillaries in at least 10 fields (200x magnification). Final data were expressed as the number of capillaries per mm 2 .…”
Section: Histological Analyses Of Mouse Heartsmentioning
confidence: 99%
“…A line crossing the centre of nuclei was drawn and the length of the segment crossing the opposite intercalated discs was then measured, in analogy to what has been described in Vliegen et al, 14 and published by us recently. 15 Vascular density was assessed by counting capillaries in at least 10 fields (200x magnification). Final data were expressed as the number of capillaries per mm 2 .…”
Section: Histological Analyses Of Mouse Heartsmentioning
confidence: 99%
“…Diseases that lead to heart failure (as well as the heart failure state itself) mimic the ageing process, in that they are characterized by an increase in oxidative and endoplasmic reticulum stress, which is exacerbated by a striking impairment in the capacity of the heart to stimulate autophagy. Autophagic flux of cardiomyocytes is markedly impaired in cardiomyocytes derived from injured or failing hearts 147–149 ; in return, pharmacological stimulation of autophagic flux can directly ameliorate oxidative stress and organellar dysfunction, thereby preventing or reversing cardiomyocyte dysfunction and mitigating the development of cardiomyopathy. 150–152 This deficiency in autophagic capacity in heart failure is related to the simultaneous impairment of SIRT1/PGC-1α and AMPK signalling 52 , 53 , 153 and enhanced activation of the Akt/mTORC1 pathway in cardiomyocytes.…”
Section: Importance Of Longevity Gene Signalling and Autophagy Modulamentioning
confidence: 99%
“… 150–152 This deficiency in autophagic capacity in heart failure is related to the simultaneous impairment of SIRT1/PGC-1α and AMPK signalling 52 , 53 , 153 and enhanced activation of the Akt/mTORC1 pathway in cardiomyocytes. 147 , 151 , 154 These derangements in longevity gene signalling is seen both experimentally and clinically.…”
Section: Importance Of Longevity Gene Signalling and Autophagy Modulamentioning
confidence: 99%
“…The study showed that cardiac BCAA catabolism and insulin signaling was impaired in human heart failure, while enhancing BCAA oxidation could improve cardiac function in the failing mouse heart [53]. A previous study has suggested that miR-22 overexpression is coupled with PP2Cm downregulation, BCAA accumulation, and mTOR hyperactivation and is possibly linked to alterations in glucose utilization and suppression of autophagy in dilated cardiomyopathy [54]. Suppression of wholebody BCAA catabolism via deletion of PP2Cm elevates circulating and cardiac BCAA levels and worsens the cardiac response to ischaemia/reperfusion injury [55].…”
Section: Discussionmentioning
confidence: 90%